Inflammation and Atherosclerosis: Current Pathogenesis - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: The inflammatory nature of atherosclerosis is well established but the agent(s) that incite inflammation in the artery wall remain largely unknown.CONTENT: Chronic inflammation is recognized as a major driving force in atherogenesis. The sites of atherosclerotic plaque development in the arterial wall are characterized by cholesterol accumulation and infiltration of peripheral blood monocytes, which gradually differentiate into macrophages. Cholesterol crystals, the common constituents of atherosclerotic lesions, include NLRP3 inflammasome activation and IL-1β secretion in human macrophages, promote an inflammatory milieu and thus drive lesion progression. Consequently, the cholesterol crystal-induced inflammasome activation may represent an important link between cholesterol metabolism and inflammation in atherosclerotic lesions. SUMMARY: The crystalline cholesterol acts as an endogenous danger signal and its deposition in arteries or elsewhere is an early cause rather than a late consequence of inflammation. The cholesterol crystal-induced inflammasome activation in macrophages may represent an important link between cholesterol metabolism and inflammation in atherosclerotic lesions. This finding provides new insights into the pathogenesis of atherosclerosis and indicates new potential molecular targets for the therapy of this disease.KEYWORDS: atherosclerosis, inflammation, neutrophil, macrophages, inflammasome, cholesterol crystal